2022
DOI: 10.3389/fmed.2022.774550
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Rapid Antigen Testing for SARS-CoV-2: The COVid-19 AntiGen (COVAG) study

Abstract: BackgroundRapid diagnostic testing for SARS-Cov-2 antigens is used to combat the ongoing pandemic. In this study we aimed to compare two RDTs, the SD Biosensor Q SARS-CoV-2 Rapid Antigen Test (Roche) and the Panbio COVID-19 Ag Rapid Test (Abbott), against rRT-PCR.MethodsWe included 2,215 all-comers at a diagnostic center between February 1 and March 31, 2021. rRT-PCR-positive samples were examined for SARS-CoV-2 variants.FindingsThree hundred and thirty eight participants (15%) were rRT-PCR-positive for SARS-C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 35 publications
0
28
2
Order By: Relevance
“…Although in laboratory-based investigations referencing the performance of the Abbott- Panbio RAD was not affected by the variants, the COVID-19 Antigen study (COVAG) in a real-world setting including 2,215 participants and 338 rRT-PCR confirmed SARS-CoV-2 positive cases Abbott-Panbio RAD test performed 72.3% sensitivity in carriers of the Alpha variant, compared to 84.0% in cases infected with wild-type SARS-CoV-2. The test-sensitivity diminishing effect of the Alpha variant was also observed in the Roche-RAD test ( 28 ). Although it is the only study indicating the lower sensitivity regarding the Abbott-Panbio RAD test for the Alpha variant, its authors cannot explain this finding and it must be taken into consideration regarding the relatively low sensitivity and positive predictive value in our results.…”
Section: Limitationmentioning
confidence: 79%
“…Although in laboratory-based investigations referencing the performance of the Abbott- Panbio RAD was not affected by the variants, the COVID-19 Antigen study (COVAG) in a real-world setting including 2,215 participants and 338 rRT-PCR confirmed SARS-CoV-2 positive cases Abbott-Panbio RAD test performed 72.3% sensitivity in carriers of the Alpha variant, compared to 84.0% in cases infected with wild-type SARS-CoV-2. The test-sensitivity diminishing effect of the Alpha variant was also observed in the Roche-RAD test ( 28 ). Although it is the only study indicating the lower sensitivity regarding the Abbott-Panbio RAD test for the Alpha variant, its authors cannot explain this finding and it must be taken into consideration regarding the relatively low sensitivity and positive predictive value in our results.…”
Section: Limitationmentioning
confidence: 79%
“…While some literature indicates that variants of concern (17,18) do not reduce the sensitivity and specificity of Ag RDTs, a recent study reported that sensitivity of the Panbio ™ Ag RDT declined significantly in individuals infected with the alpha variant (53.0%) compared to those with non-alpha variants (89.0%) even after adjusting for viral load (p <0.002) [ 24 ] as was also demonstrated by Wertenauer et . al in the COVAG study [ 25 ]. Mutations occurring in the N protein of the Alpha variant may not be detected by the Panbio ™ Ag RDT [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of PanBio was slightly higher (60.87 vs 56.8%), while the sensitivity of Standard Q RDT was almost similar (59.83 vs. 60.4%) compared to a similar study conducted in Germany 7 . However, the sensitivities were markedly lower compared to a similar study conducted in Switzerland, which showed a sensitivity of 85.5 and 89% for PanBio and Standard Q, respectively 14 .…”
Section: Discussionmentioning
confidence: 61%
“…RT-PCR-based assays are considered the gold standard due to their high sensitivity and specificity, allowing detection even in asymptomatic individuals [5] . However, the fallacies of genomebased techniques include needing trained personnel, specialized laboratories, long result awaiting time (hours to days), and increased cost [6,7] . Although the accuracy and reliability of RDTs are lower than PCR's, they are widely used as they provide rapid results (within minutes), are inexpensive, simple to perform, and do not need specialized expertise (self-testing is possible) [8] .…”
Section: Introductionmentioning
confidence: 99%